Pengaruh Penggunaan Media Clock Set terhadap Hasil Belajar Matematika - Arif Rahman Hakim (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
The aim of this research is to obtain empirical data on the influence of using clock set media towards math learning outcomes. This research used the experiment method at second grade of SD Islam Al Azhar 1 Kebayoran Baru, Jakarta Selatan. In this research was done by taking two classes; experiment class and control class, Each class consists of 36 students. The instrument that is used in this research is test with using multiple choice questions which have been validated empirically. Data analysis used in this research is t test. The result of this research is there is significant influence between using of clock set media towards math learning outcomes at second grade of SD Islam Al Azhar 1 Kebayoran Baru, Jakarta Selatan.